Hydrothermal and Cold Spring Water and Primary Productivity Effects on Magnesium Isotopes: Lake Myvatn, Iceland - Pogge von Strandmann, Philip A. E.; Burton, Kevin W.; Opfergelt, Sophie; Eiríksdóttir, Eydís S.; Murphy, Melissa J.; Einarsson, Arni; Gislason, Sigurdur R. (Frontiers in Earth Science, 2020)
Lake Myvatn, Iceland, is one of the most biologically productive lakes in the northern hemisphere, despite seasonal ice cover. Hydrothermal and groundwater springs make up the dominant source to this lake, and we investigate their Mg isotope ratio to assess the effect of mid-ocean ridge hydrothermal springs, which are the primary modern sink of seawater magnesium. We also examine a time series in the only outflow from this lake, the Laxa River, to assess the effects of seasonal primary productivity on Mg isotopes. In the hydrothermal waters, there is a clear distinction between cold waters (largely unfractionated from primary basalt) and relatively hot waters, which exhibit over 1‰ fractionation, with consequences for the oceanic mass balance if the hydrothermal removal of Mg is not fully quantitative. The outflow Mg isotopes are similar to basalts (26Mg = -0.2 to -0.3) during winter, but reach a peak of ~0‰ in August. This fractionation corresponds to calcite precipitation during summer in Lake Myvatn, preferentially taking up light Mg isotopes, and driving the residual waters isotopically heavy as observed, meaning that overall the lake is a CO2 sink.